Hepatic artery thrombosis following living donor liver transplantation: A 14‐year experience at a single center. (2nd July 2020) - Park, Jangho; Kim, Seong Hoon; Park, Sang‐Jae
Abstract: Background: Hepatic artery thrombosis (HAT) following liver transplantation is a serious complication that may lead to graft loss and ultimately death. Retransplantation and surgical recanalization for HAT have traditionally been the predominant methods of treatment. However, with the development of endovascular therapies, including percutaneous transluminal angioplasty, thrombolysis, and stent insertion, these methods are now mainly used because they allow prompt management. Methods: From January 2005 to December 2018, 756 patients underwent liver transplantation at our institution, and 14 of those patients developed early HAT. All patients underwent endovascular arteriography immediately after the diagnosis of thrombosis. We retrospectively reviewed the 14 patients with HAT. Results: Hepatic artery thrombosis following liver transplantation occurred in 14 patients (1.9%) within 1 month after transplantation. The final success rate of radiological intervention was 71.4% (n = 10). Of the four patients in whom intravenous procedures failed, two ultimately underwent retransplantation and one patient underwent surgical revision of the hepatic artery. Bleeding and rebound thrombosis after the intervention occurred in three patients (21.4%) and four patients (28.6%), respectively. Conclusion: Endovascular procedures can be safe and provide prompt recovery in early HAT patients following liver transplantation to prevent graft loss and patient mortality despite the presence of hemorrhage and rebound thrombosis. Immediate endovascular procedure after the end of the transplantation is also necessary in intraoperatively developed HAT instead of several trials of arterial anastomoses to revascularization. Abstract : Highlight Park and colleagues retrospectively reviewed 14 cases of hepatic artery thrombosis following living donor liver transplantation in 756 patients at a single center over 14 years. The salient finding is that immediate endovascular procedures even within 24 hours of transplantation are feasible as initial treatment before surgical revision or retransplantation.